Communications to Promote Interest and Confidence in COVID-19 Vaccines. Issue 6 (July 2022) - Thorpe, Alistair; Fagerlin, Angela; Drews, Frank A.; Butler, Jorie; Stevens, Vanessa; Riddoch, Marian S.; Scherer, Laura D.
Purpose: Communicating about COVID-19 vaccine side effects and efficacy is crucial for promoting transparency and informed decision-making, but there is limited evidence on how to do so effectively. Design: A within-subjects experiment. Setting: Online survey from January 21 to February 6, 2021. Subjects: 596 US Veterans and 447 non-Veterans. Intervention: 5 messages about COVID-19 vaccine side effects and 4 messages about COVID-19 vaccine efficacy. Measures: COVID-19 vaccine interest (1 = "I definitely do NOT want the vaccine" to 7 = "I definitely WANT the vaccine" with the midpoint 4 = "Unsure"). Confidence about COVID-19 vaccine efficacy (1= "Not at all confident, " 2 = "Slightly confident, " 3 = "Somewhat confident, " 4 = "Moderately confident, " 5 = "Extremely confident"). Results: Compared to providing information about side effects alone ( M = 5.62 [1.87]), messages with additional information on the benefits of vaccination (M = 5.77 [1.82], P < .001, d z = .25), reframing the likelihood of side effects (M = 5.74 [1.84], P < .001, d z = .23), and emphasizing that post-vaccine symptoms indicate the vaccine is working (M = 5.72 [1.84], P < .001, d z = .17) increased vaccine interest. Compared to a vaccine efficacy message containing verbal uncertainty and an efficacy range ( M = 3.97 [1.25]), messages conveying verbal certainty with an efficacy range ( M = 4.00 [1.24], P = .042, d z =.08), verbal uncertainty focused on the upper efficacy limit ( M = 4.03 [1.26], P < .001, d z = .13), and communicating the point estimate with certainty ( M = 4.02 [1.25], P < .001, d z = .11) increased confidence. Overall, Veteran respondents were more interested ( M Veterans = 5.87 [1.72] vs M NonVeterans = 5.45 [2.00], P < .001, d = .22) and confident ( M Veterans = 4.13 [1.19] vs M NonVeterans = 3.84 [1.32], P < .001, d = .23) about COVID-19 vaccines than non-Veterans. Conclusions: These strategies can be implemented in large-scale communications (e.g., webpages, social media, and leaflets/posters) and can help guide healthcare professionals when discussing vaccinations in clinics to promote interest and confidence in COVID-19 vaccines.